Schiff's bases of quinazolinone derivatives: Synthesis and SAR studies of a novel series of potential anti-inflammatory and antioxidants. Issue 5 (1st March 2015) - Rakesh, K.P.; Manukumar, H.M.; Gowda, D. Channe
Graphical abstract